Evaluation of Olibanum Resin as Microencapsulating Agent for Controlled Release of Glimepiride - Chowdary, K.P.R.; Panguluri, Srinivas (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate olibanum resin, a natural lipophilic polymer for its application as microencapsulating agent for controlled release of glimepiride. Controlled release formulations are needed for glimepiride for better control of blood glucose levels to prevent hypoglycemia, enhance clinical efficacy and patient compliance. Olibanum resin coated microcapsules of glimepiride were prepared by industrially feasible emulsification-solvent evaporation method and the microcapsules were evaluated for controlled release. The resin coated microcapsules prepared are spherical, discrete, free flowing and multinucleate monolithic type. Microencapsulation efficiency was in the range 84-108 %. Glimepiride release from the microcapsules was slow over 24 h and depended on core:coat ratio, wall thickness and size of the microcapsules. Drug release from the microcapsules was by non-fickian diffusion mechanism. Good linear relationship was observed between wall thickness of the microcapsule and release rate. Olibanum resin was found suitable as a new microencapsulating agent and the resin coated microcapsules exhibited good controlled release characteristics. Glimepiride release from the olibanum resin coated microcapsules, MC 2 (size 20/30) fulfilled the theoretical controlled release needed for glimepiride based on its pharmacokinetics.